Mechanism and Inducing Factors of Rockburst Events of Roadways Under Ultrathick Strata - Hao, Zhen; Sun, Guangzhong; Zhang, Guohua (Frontiers in Earth Science, 2022)
The overlying strata of Yima coalfield are ultra thick conglomerate. Aiming at the problem of frequent occurrence of rockburst events in central Yima coalfield during 2006 to 2015, the characteristics of rockburst events, microseismic (MS) monitoring and rockburst events inducing factors were analyzed through data mining and field investigation methods. The results showed that the rockburst events in roadway were mainly occurred during mining of the working face, and they occurred at a large buried depth and were within the influence of mining stress, accompanied by abrupt energy release. The occurrence of rockburst in roadways was accompanied by a sudden release of energy. The ultra thick strata and the fault nearby was the key influence factor of rockburst events. The stress field of roadway surrounding rock was changed because of the mining disturbance, roadway repair and maintenance, blasting, which would change the regional stress fields in the surrounding rock and induce roadway rockburst events. The characteristics of rockburst event were floor heave, sharp convergence of two side walls, severe damage of supporting body, and even closure of roadway. The occurrence of rockburst can be prevented by reducing mining speed and injecting water into coal seam.